Sustaining Exemplary Practice: Leading Through the Lens of Organizational Learning. (November 2020) - Lyman, Bret; Parchment, Joy
Abstract : Nurse leaders must be proficient at fostering organizational learning within their teams and throughout their companies. Organizational learning can be achieved by creating a culture conducive to learning, integrating learning practices into the team's routines, and leveraging the impact of learning by cultivating a strong, vibrant institutional memory. Authors describe the concept of organizational learning, provide strategies for fostering a culture where organizational learning thrives, and underscore the nurse leaders' role in leading organizations to achieve and sustain exemplary practice.